KOMPETENSI DAN PROSPEK PERADILAN TATA USAHA NEGARA DALAM MEMERIKSA HASIL PELAKSANAAN EXECUTIVE PREVIEW TERHADAP RANCANGAN PERATURAN DAERAH - Aloysius Eka Kurnia (Dialogia Iuridica, 2020)
The Law on Local Government gives the authority for state administration officials to evaluate the Draft of Regional Regulation in order to prevent disharmony between Regional Regulations and other regulations. The authority to evaluate this draft of regional regulation in the practice of state administration in Indonesia is exercised by the Minister of Home Affairs and the local Governor. When the Draft of Regional Regulation is canceled by a state administration official through a State Administration Decree, the legality should be tested through the State Administrative Court. In this case it is important to review the competence of the State Administrative Court in examining disputes over the evaluation results of the Draft of Regional Regulation involving the central and local governments. This research is a normative legal research by using primary and secondary legal materials as well as legislation and conceptual approaches. The purpose of this research is to analyze the prospect of a State Administration lawsuit by a government agency against another government agencies in relation to protecting the rights of the community.